2012
DOI: 10.2460/ajvr.73.1.146
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory mechanics and results of cytologic examination of bronchoalveolar lavage fluid in healthy adult alpacas

Abstract: Pulmonary function testing was tolerated well in nonsedated untrained alpacas. Bronchoalveolar lavage in alpacas yielded samples with adequate cellularity that had a greater abundance of neutrophils than has been reported in horses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 46 publications
3
3
0
Order By: Relevance
“…In the present study, the decreased fraction of macrophages in TW and BAL from diseased camels is in line with reports from other species, including human (Rose & Knox, 2007), horses (Rossi et al, 2018), cattle (Kokotovic, Friis & Ahrens, 2007, and alpaca (Pacheco, Mazan & Hoffman, 2012). The lower frequency of macrophages in diseased animals may be a result of the increased accumulation of neutrophils in the respiratory secretions.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In the present study, the decreased fraction of macrophages in TW and BAL from diseased camels is in line with reports from other species, including human (Rose & Knox, 2007), horses (Rossi et al, 2018), cattle (Kokotovic, Friis & Ahrens, 2007, and alpaca (Pacheco, Mazan & Hoffman, 2012). The lower frequency of macrophages in diseased animals may be a result of the increased accumulation of neutrophils in the respiratory secretions.…”
Section: Discussionsupporting
confidence: 92%
“…Similar to their distribution in healthy horses (Malikides et al, 2003), neutrophils were found in higher proportions in TW than in BAL fluids from healthy camels. The increased fraction of neutrophils in TW and BAL fluids from camels with respiratory diseases is also in line with findings in respiratory diseased horses (Rossi et al, 2018), donkeys (Shawaf, 2019), cattle (Kokotovic, Friis & Ahrens, 2007), and alpaca (Pacheco, Mazan & Hoffman, 2012).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…In camels with respiratory disease, BALF samples contained higher total immune cell numbers than healthy camels, which is similar to findings in respiratory diseased cattle and horses [15,22,[60][61][62]. Similarly, the decrease in macrophages with expansion in the fraction of granulocytes is also in line with findings in respiratory diseased cattle [21], horses [14,60], donkeys [61], and other camelids [24]. Although the proportion of the total lymphocyte population in camel BALF was not affected by respiratory disease, BALF samples from diseased camels contained higher percentages of CD4+ T cells and B cells, than healthy animals.…”
Section: Discussionsupporting
confidence: 83%
“…Cytological, microbiological, and immunological evaluation of BALF enables the detection of subclinical respiratory disease and the identification of the severity grade, and stage of inflammatory reactions in the respiratory tract [ 18 , 19 ]. BALF has been proven as a valuable sample for investigating tissue resident immune cells in the respiratory tract of several species including mankind [ 17 ], horses [ 20 ], cattle [ 21 , 22 ], sheep [ 23 ], alpaca [ 24 ], pigs [ 25 ], dogs [ 26 , 27 ], and cats [ 28 ]. Also in the dromedary camel, the BAL procedure has been recently used for the collection of samples for cytological analysis [ 29 ].…”
Section: Introductionmentioning
confidence: 99%